I.E. Repin academy education in mongolian printmaking arts (Mongolian Journal of Arts and Culture, 2023)
Academism emerged in Europe from XVI to XIX centuries, characterized by a dogmatic adherence to the external forms of classical art. This movement played a pivotal role in the organization of art education and the standardization of the classical tradition, viewed as an ‘eternal’ law and system. During XVII and XVIII centuries, Academism extended its influence to countries such as England, France, and Russia, with the Imperial Russian Academy standing out as the most powerful and influential. Throughout the history of global visual arts education, there has been an intense debate surrounding the concept of academic training or academism, and it is evident that this discussion will persist in the future. In the history of global visual arts education, a vigorous debate has unfolded around the concept of academic training or academism, and it is evident that this discourse will persist into the future. The Russian Imperial Academy of Fine Arts, having matured within Western art traditions for centuries, has successfully navigated into the XXI century by blending tradition and innovation in sync with the pace of time. Since L.Gavaa, the first Mongolian artist, undertook studies at the Academy of Fine Arts in 1952, 70 artists have graduated, exemplifying the clear formation and development of classical education in Mongolian fine arts. Our study will focus on the teaching methodologies of the following two artists and educators who have inherited I.E. Repin’s school of art, passing it down to the next generation, and who continue this tradition and contribute to the education of Mongolian visual arts - Ya. Oyunchimeg, an Honored Worker of the Art of Mongolia and Associate Professor, Artist, and Z. Uyanga, a teacher and an Award-winning artist of the Mongolian Craftsmen’s Union Committee.И.Е.Репиний академийн дэг сургалт монголын Бар зургийн урлагтХураангуй: Академизм бол сонгодог урлагийн гадаад хэлбэрийг догматик баримтлах үндсэн дээр XVI-XIX зуунд Европт үүсэж хөгжсөн. Академизм нь урлагийн боловсролыг системчлэх, сонгодог уламжлалыг нэгтгэхэд шийдвэрлэх нөлөө үзүүлсэн, үүнийг “мөнхийн” хууль тогтоомж, систем гэж үздэг байв. XVII-XVIII зуунд Англи , Франц, Орос болон бусад оронд дэлгэрч, тэдний дунд Орос ын Эзэн Хааны Академи хамгийн их эрх мэдэлтэй нөлөө бүхий байсан . Дэлхийн дүрслэх урлагийн боловсролын түүхэнд академик дэг сургалт буюу академизм хэмээх ойлголтын талаар ихээхэн ширүүн маргаан өрнөсөөр ирсэн, энэхүү байдал цаашид ч үргэлжлэх нь ойлгомжтой юм. Зуу зуун жилээр өрнөдийн урлагт төлөвшин хөгжиж ирсэн Оросын Эзэн Хааны Дүрслэх урлагийн академи нь цаг хугацааны аясаар уламжлал , шинэчлэлийг хослуулан хөгжсөөр XXI зуунд хүрч иржээ. Тус Дүрслэх урлагийн академид монголын анхны уран бүтээлч Л.Гаваа 1952 онд суралцсанаас өдийг хүртэл 70 гаруй уран бүтээлчид суралцаж төгссөн нь монголын дүрслэх урлагт сонгодог дэг сургалт бүрэлдэн тогтох үндэс суурь болж өгсөн юм. Эд үгээ И.Е.Репиний академийн дэг сургалтыг хойч үед ээ өвлүүлж үлдээсэн уран бүтээлч багш нар болон одоо ч энэ дэг сургалт ыг хойч үедээ уламжлуулан, монголын дүрслэх урлагийн боловсролд хүчин зүтгэж буй уран бүтээлчдийн төлөөлөл болох Монгол улсын Урлагийн гавьяат зүтгэлтэн дэд профессор , зураач Я.Оюунчимэг, Монголын Урчуудын эвлэлийн хорооны шагналт зураач, багш З.Уянга нарын сургалтын арга зүйг судлах болно.Түлхүүр үг: академизм, бар зураг, уламжлал, дардас, торгон бар